Cemented total hip arthroplasty following acetabular fracture. (October 2017) - Scott, C. E. H.; MacDonald, D.; Moran, M.; White, T. O.; Patton, J. T.; Keating, J. F.
Abstract : Aims: To evaluate the outcomes of cemented total hip arthroplasty (THA) following a fracture of the acetabulum, with evaluation of risk factors and comparison with a patient group with no history of fracture. Patients and Methods: Between 1992 and 2016, 49 patients (33 male) with mean age of 57 years (25 to 87) underwent cemented THA at a mean of 6.5 years (0.1 to 25) following acetabular fracture. A total of 38 had undergone surgical fixation and 11 had been treated non-operatively; 13 patients died at a mean of 10.2 years after THA (0.6 to 19). Patients were assessed pre-operatively, at one year and at final follow-up (mean 9.1 years, 0.5 to 23) using the Oxford Hip Score (OHS). Implant survivorship was assessed. An age and gender-matched cohort of THAs performed for non-traumatic osteoarthritis (OA) or avascular necrosis (AVN) (n = 98) were used to compare complications and patient-reported outcome measures (PROMs). Results: The mean time from fracture to THA was significantly shorter for patients with AVN (2.2 years) or protrusio (2.2 years) than those with post-traumatic OA (9.4 years) or infection (8.0 years) (p = 0.03). Nine contained and four uncontained defects were managed with autograft (n = 11), bulk allograft (n = 1), or trabecular metal augment (n = 1). Initial fracture management (open reduction and internal fixation or non-operative), timing of THA (> /< one year), and age (> /< 55 years) had no significant effect on OHS or ten-year survival. Six THAs were revised at mean of 12 years (5 to 23) with ten-year all-cause survival of 92% (95% confidence interval 80.8 to 100). THA complication rates (all complications, heterotopic ossification, leg length discrepancy > 10 mm) were significantly higher following acetabular fracture compared with atraumatic OA/AVN and OHSs were inferior: one-year OHS (35.7 v ersus 40.2, p = 0.026); and final follow-up OHS (33.6 v ersus 40.9, p = 0.008). Conclusion: Cemented THA is a reasonable option for the sequelae of acetabular fracture. Higher complication rates and poorer PROMs, compared with patients undergoing THA for atraumatic causes, reflects the complex nature of these cases. Cite this article: Bone Joint J 2017;99-B:1399–1408.